Dampak Media Pembelajaran Online Terhadap Motivasi Belajar Siswa Madrasah Ibtidaiyah - Maulana, Muhammad Rizki; Sholihin, Muhammad Riyadus; Nurkholik, Dhefi; Permana, Hadi (Jurnal Pelita Teknologi, 2023)
The advent of online learning media has brought about significant changes in the educational landscape, particularly in Madrasah Ibtidaiyah settings. This study delves into the impacts of online learning media on students' learning motivation in Madrasah Ibtidaiyah. Through a mixed-method approach encompassing surveys and interviews, data were gathered from a sample of 200 students. The findings reveal a nuanced relationship between online learning media and student motivation. While the convenience and accessibility of online platforms enhance motivation, challenges such as technical issues and limited interaction can dampen motivation. Moreover, the study highlights the need for a balanced integration of online and offline learning strategies to sustain and boost students' motivation in Madrasah Ibtidaiyah.